Primary cilium-dependent autophagy in the response to shear stress. (17th December 2021) - Morel, Etienne; Dupont, Nicolas; Codogno, Patrice
Abstract : Mechanical forces, such as compression, shear stress and stretching, play major roles during development, tissue homeostasis and immune processes. These forces are translated into a wide panel of biological responses, ranging from changes in cell morphology, membrane transport, metabolism, energy production and gene expression. Recent studies demonstrate the role of autophagy in the integration of these physical constraints. Here we focus on the role of autophagy in the integration of shear stress induced by blood and urine flows in the circulatory system and the kidney, respectively. Many studies highlight the involvement of the primary cilium, a microtubule-based antenna present at the surface of many cell types, in the integration of extracellular stimuli. The cross-talk between the molecular machinery of autophagy and that of the primary cilium in the context of shear stress is revealed to be an important dialog in cell biology.